(untitled) (Research, Society and Development, 2024)
Ligninolytic enzymes from differents Basidiomycete fungi on different substrates demonstrate microorganisms biotechnological potential on agro-industrial byproducts. The aim of this study was to evaluate the use of enzymatic extracts of Lentinus tigrinus and Trametes villosa produced by semi-solid fermentation (SSF) for processing sisal coproduct and sugarcane bagasse. The strains were evaluated for RBBR test to confirm enzymes production and subsequently subcultured for 7 days until visible growth of the mycelium. For the SSF, 48 Erlenmeyers distributed in different treatments were used. The enzymatic extract was obtained and added in BC and CDS for further Bromatological analysis. The cultivation methods used were satisfactory in terms growth fungal and ligninase production from RBBR test. The fungi showed good potential in agro-industrial by-products lignocellulosic reduction. The enzyme synthesis behavior of the fungi was different, demonstrating to be in the initial days for Lentinus tigrinus and at 14 days for Trametes villosa.